2020
DOI: 10.1002/gps.5408
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors for postoperative delirium in adult patients after hip fracture surgery: a systematic review and meta‐analysis

Abstract: Objectives: Postoperative delirium (POD) is the most common complication in patients after hip fracture surgery, and the incidence of POD is associated with mortality and disability in patients following hip fracture surgery. Therefore, this study aimed to identify the individual as well as anesthetic and operative risk factors associated with the POD in adult patients after hip fracture surgery. Methods: We searched relevant articles published to February 2020 in Cochrane Library, PubMed, and Embase. Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 68 publications
(170 reference statements)
4
78
1
4
Order By: Relevance
“…Based on the propensity scores, postoperative delirium patients were matched in 1 : 1 ratio to normal patients using greedy nearest neighbor matching algorithm without replacement and match tolerance equal to 0.01. Refer to the previous study; when fitting the PSM model, 14 baseline characteristics which were proven to be risk factors of POD were used as baseline covariates to participate in the analysis: age, sex, smoking, drinking, diabetes, hypertension, coronary heart disease, history of mental illness or psychotropic drug use, blood transfusion, anesthesia, surgical approach, surgical grade, EF, and LVD [ 8 , 13 15 ]. Standardized differences for categorical variables before and after PSM were evaluated by chi-square, but for the continuous variable, independent T test was used.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the propensity scores, postoperative delirium patients were matched in 1 : 1 ratio to normal patients using greedy nearest neighbor matching algorithm without replacement and match tolerance equal to 0.01. Refer to the previous study; when fitting the PSM model, 14 baseline characteristics which were proven to be risk factors of POD were used as baseline covariates to participate in the analysis: age, sex, smoking, drinking, diabetes, hypertension, coronary heart disease, history of mental illness or psychotropic drug use, blood transfusion, anesthesia, surgical approach, surgical grade, EF, and LVD [ 8 , 13 15 ]. Standardized differences for categorical variables before and after PSM were evaluated by chi-square, but for the continuous variable, independent T test was used.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, glaucoma surgery was significantly associated with an increase in the risk for all-cause mortality, mortality caused by cancer, and accident or trauma-related mortality in patients with ACG, who are known to have an approximately three-fold increased risk of having severe binocular vision loss compared to patients with OAG 28 , 29 . In a recent meta-analysis, the pooled relative risk of mortality due to visual impairment was 1.36 30 . In another national sample cohort study, the blindness group showed a 1.54 times increased risk of mortality compared with the control group 4 .…”
Section: Discussionmentioning
confidence: 99%
“…While the etiological pathways that result in PND are still not precisely known, the field has progressed since the initial reports which emphatically stated that general anesthetics were the culprit [1,29]. However, the risk of developing postoperative delirium does not differ whether the patient receives a general or a regional anesthetic [36], and in fact may be greater for those receiving regional anesthesia [37], thereby shedding doubt on the putative causal role of general anesthesia [38]. Furthermore, in cardiac surgery it was noted that the risk of developing cognitive decline postoperatively did not differ depending on whether patients received on-vs. off-pump cardiac surgery [39]; therefore, the possible deleterious effects of the "pump" as a cause of "pumphead" have also been rejected as a reason for cognitive decline in cardiac surgical patients.…”
Section: Inflammatory Pathogenesis Of Perioperative Neurocognitive Disordersmentioning
confidence: 99%